(untitled) (Al-Mansour Journal, 2022)
the presence of low order harmonics in grid-connected renewable-energy inverter systems is undesirable and has many adverse impacts on the entire systems, so it is necessary to eliminate these harmonics to increase the system efficiency and stability. In this paper, the principle of power flow between the grid utility and the inverter(s) is reported and a single reference inverter is used employing conventional selective harmonic elimination pulse width modulation (SHEPWM) to eliminate the 5th and 7th harmonics. By adjusting a pre- calculated phase-shift angle between parallel inverters, it is also possible to eliminate other low order harmonics without any increase in the switching frequency. This approach has been applied for high power grid-connected voltage source inverter systems (VSI) supplied by renewable energy sources( such as wind energy, photovoltaic system,…etc) which are very sensitive to any increase in the switching frequency. Single, two, and four parallel VSI grid connected systems are investigated and simulated in PSPICE and MATLAB software